Systemic problems affecting co-innovation in the New Zealand Agricultural Innovation System: Identification of blocking mechanisms and underlying institutional logics. (1st March 2016) - Turner, James A.; Klerkx, Laurens; Rijswijk, Kelly; Williams, Tracy; Barnard, Tim
Highlights: A combined structural-functional analysis of the New Zealand AIS. The New Zealand AIS is overly focused on science-driven knowledge development. Three key blocking mechanisms hinder co-innovation. Institutional logics perpetuate linear orientation of AIS. Transformative systemic instruments are key. Abstract: This study identifies systemic problems in the New Zealand Agricultural Innovation System (AIS) in relation to the AIS capacity to enact a co-innovation approach, in which all relevant actors in the agricultural sector contribute to combined technological, social and institutional change. Systemic problems are factors that negatively influence the direction and speed of co-innovation and impede the development and functioning of innovation systems. The contribution in the paper is twofold. Firstly, it combines both innovation system functions and systemic problems in an integrated analysis to asses an AIS at a country level, which has not been done previously in AIS literature. Secondly, it deepens the generic literature on structural-functional innovation systems analysis by looking at the interconnectedness between systemic problems and how these create core blocking mechanisms linked to the prevalent institutional logics (historically built-up and persistent structures and institutional arrangements) of the AIS. Results indicate that the existing New Zealand AIS has three main blocking mechanisms related to three institutional logics: (i) competitive science in silos, (ii) laissez faire innovation, and (iii) science centered innovation. These findings resemble weaknesses of AIS in other countries, and provide supportive evidence that co-innovation principles in many places have not yet been translated into agricultural innovation policies due to persistent and interlocked blocking mechanism and institutional logics. They point to the absence of effective systemic innovation policy instruments that pro-actively stimulate and support co-innovation. These instruments facilitate the counteracting of individual systemic problems and have a more transformative ambition; tackling the key institutional logics that hinder co-innovation, and hence supporting 'structural system innovation'.